The Instilling of Ethical Language Values for the Students through Folklore at Sekolah Kebangsaan Padung Mart, South Thailand - Purba, Happy Sri Rezeki; Harahap, Eli Marlina; Harahap, Erlina; Lubis, Wiwin Wahyuni; Aritonang, Syahrudin; Hasibuan, Iskandar Safri; Harahap, Qorry Hilmiyah; Nasution, Ismawal Pebriani (Bhinneka Publishing, 2025)
This community service program aimed to develop ethical language values among students through storytelling and folklore-based learning. The activity was implemented at Ban Phadung Mart School, Southern Thailand, involving 20 students over three sessions. The program applied interactive storytelling as a medium to integrate linguistic, cultural, and moral learning. The community service was designed as a participatory educational intervention that emphasized the use of folklore to internalize ethical concepts such as honesty, respect, responsibility, and empathy. Data were collected through observation, reflection journals, and interviews with students and teachers. The results indicated a significant improvement in students’ understanding of moral values and their ability to use English to express those values. The storytelling sessions not only improved language skills but also cultivated ethical awareness, social responsibility, and appreciation of local culture. The project highlights the importance of folklore as a pedagogical tool in developing ethical and linguistic competence in EFL contexts.